Inclusion and Autism: Is inclusion in mainstream education appropriate for pupils with Autistic Spectrum disorders? - Taylor, Rachael (2015)
Abstract The issue of inclusion remains a controversial one, with critics arguing that a mainstream environment is simply not appropriate for all pupils, especially those diagnosed with Autistic Spectrum Disorder (ASD). Thus the aim of this study is to gain further insight into this topic by using the personal experiences of one individual to highlight and explore some of the main issues. A semi-structured interview was conducted with the parent of a young boy with ASD who had recently been moved from a mainstream classroom to more specialist provision. Three main themes emerged from the research; difficulties with social interaction, problems with the mainstream environment and attitudes within the mainstream. These themes were then used to explore the literature surrounding the topic and discuss how they impacted on the process of inclusion. The implications of the findings were then considered and related to current practice. Various measures were suggested that could help make the mainstream classroom a more suitable environment for some pupils with ASD. However, it was ultimately concluded that no amount of adaptations could make the mainstream an appropriate educational setting for all pupils with ASD and that specialist provision would still be necessary in some cases. Key Words: Autistic Spectrum Disorder, Inclusion, Mainstream